2003
DOI: 10.1081/jas-120017212
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Prescribed Treatment for Asthma: Evidence from Pharmacy Benefits Data

Abstract: In clinical practice settings, patients initiating LTRA monotherapy have about twice the adherence as patients initiating ICS or ILBA monotherapy. Because adherence to treatment is a critical component of treatment response, it is important to consider this factor in the prescription of oral vs. inhaled asthma medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(73 citation statements)
references
References 18 publications
6
64
0
3
Order By: Relevance
“…This observation concurred with the findings of other studies, which indicated that adherence was poor for inhaled medications, both in general and in comparison with oral medications. [28][29][30] As is true for other therapeutic areas (ie, hyperlipidemia, hypertension), medication adherence has been crucial to obtaining the beneficial effects of asthma treatment, and poor adherence to medication has been associated with detrimental health outcomes for patients with asthma. 31,32 In this study, for patients who were adherent (MPR ≥0.8) to their controller medication regimen, the risk of INP/ED visits was lower for patients receiving ICS monotherapy than for those receiving LM.…”
Section: Discussionmentioning
confidence: 99%
“…This observation concurred with the findings of other studies, which indicated that adherence was poor for inhaled medications, both in general and in comparison with oral medications. [28][29][30] As is true for other therapeutic areas (ie, hyperlipidemia, hypertension), medication adherence has been crucial to obtaining the beneficial effects of asthma treatment, and poor adherence to medication has been associated with detrimental health outcomes for patients with asthma. 31,32 In this study, for patients who were adherent (MPR ≥0.8) to their controller medication regimen, the risk of INP/ED visits was lower for patients receiving ICS monotherapy than for those receiving LM.…”
Section: Discussionmentioning
confidence: 99%
“…This percentage shows that still many asthmatic patients are not adherent to their inhalational medications. Previously done research shows that, adherence to inhaled therapies is worse than that seen with oral or injected therapies in patients with asthma in different age groups [18][19][20][21]. According to study conducted in turkey to assess the effects of training on the correct use of inhalation devices, only 55.3% of patients were able to correctly use the devices before training but after the training, the rate of correct use increased to 83.7% [22].…”
Section: Discussionmentioning
confidence: 99%
“…[56][57] Such trials do not address the practical issues that impact on effectiveness in real-life primary care practice such as inadequate inhalation technique, 58 perceived side effects of steroids, 59 patient preference for regular treatment, and the impact of adherence. 60 …”
Section: S5mentioning
confidence: 99%